Analysis of laminated crack defect in the upsetting process of heavy disk-shaped forgings. (January 2016) - Wang, Minting; Li, Dongying; Wang, Fan; Zang, Xinliang; Li, Xuetong; Xiao, Hong; Du, Fengshan; Zhang, F.C.; Jiang, Zhengyi
Abstract: Using nonlinear finite element method, a thermo-mechanical coupled simulation model for the formation mechanism of the laminated crack defect has been established in the upsetting of heavy disk-shaped forgings. Through numerical simulation, the distributions of stress, equivalent strain and strain rate were analysed. Meanwhile the distribution diagram of stress state evolution was obtained, and the uncoordinated deformation, under tri-lateral compression, is determined as the main reason leading to laminated crack defect. To reveal the characteristics of the uncoordinated deformation, the variations of each variable and its gradient in numerical simulation were presented, and a combined prediction model of laminated crack defect were proposed based on degree of deformation and gradient of deformation speed. Subsequently, the morphology and distribution of laminated crack were obtained in the centre of forging using the prediction model. Comparison of calculation results and experimental data indicates that both of them match well. In addition, the effect of friction coefficient on the deformation is also presented. The results show that the decreasing of friction coefficient is an effective measure to restrain the laminated crack defect. Highlights: Thermo-mechanical coupled simulation model is established in the upsetting of heavy disk-shaped forging. Uncoordinated deformation is the main reason of laminated crack defect under tri-lateral compression. Combined prediction model of laminated crack defect based on degree of deformation and gradient of deformation speed is proposed. The decreasing of friction coefficient is an effective measure to restrain the laminated crack defect.